LASIK after retinal detachment surgery. Issue 5 (1st May 2003) - Sinha, R; Dada, T; Verma, L; Chaudhury, D B; Tandon, R; Vajpayee, R B
Abstract : Aim: To assess the efficacy and safety of laser in situ keratomileusis (LASIK) for correction of myopic refractive errors in eyes which have previously undergone retinal detachment surgery. Methods: In a prospective, non-comparative case series, 10 eyes of nine patients who had a myopic refractive error and had previously undergone retinal detachment surgery underwent LASIK surgery according to the standard surgical protocol. The surgery could be completed in eight eyes and in two eyes it was aborted intraoperatively. The parameters evaluated included the uncorrected visual acuity, best corrected visual acuity, refraction, detailed fundus evaluation with indirect ophthalmoscope, slit lamp biomicroscopy, and corneal pachymetry. Any intraoperative or postoperative complications were recorded. Follow up visits were scheduled at day 1, 1 week, 1 month, 3 months, and 6 months after LASIK. Results: Eight eyes underwent successful LASIK surgery. The mean spherical equivalent before surgery was −5.436 (SD 1.6) dioptres (D), which was reduced to +0.42 (0.65) D, −0.07 (1.32) D, −0.06 (1.39) D, and −0.06 (0.65) at 1 week, 1 month, 3 months, and 6 months respectively after LASIK. The uncorrected visual acuity improved in all the eyes and the best corrected visual acuity improved or remained same in all the eyes. There was no retinal complication after LASIK. Conclusion: LASIK may be used to correct refractive errors in eyes that have undergone retinal detachment surgery. However, scarred conjunctiva in such cases may prevent generation of optimal suction for the microkeratome.